Comparative Analysis of Runoff and Evaporation Assessment Methods to Evaluate Wetland–Groundwater Interaction in Mediterranean Evaporitic-Karst Aquatic Ecosystem - Gil-Márquez, José Manuel; Andreo-Navarro, Bartolomé; Mudarra-Martínez, Matías (MDPI, 2021)
This work compares the applicability of several free-surface evaporation and runoff equations in simulating water level variations of small Mediterranean wetlands. The Amarga and Jarales wetland are two pilot sites with an evaporite-karst genesis located in southern Spain. The water level was continuously recorded in both wetlands, and exhaustive weather monitoring was performed. The combined datasets have permitted quantification of the surficial elements of their water budget (precipitation, runoff, and evaporation). Several campaigns of groundwater level measurements were also done to characterize the direction of groundwater flows. The morphometrical analysis of the Jarales wetland was accurately performed based on a LiDAR dataset. A total of 225 limnimetric simulations of the Jarales (90) and Amarga (135) wetlands were performed, combining different evaporation and runoff equations. During the study period, the curve number method, coupled with the Penman equation, reached the Jarales wetland’s best calibrations. The Vardavas–Fountoulakis modification of the Penman model fit better with the Amarga wetland record. The obtained results permit specification of the water budget of both wetlands during several years and confirm that the groundwater–surface water relationship affects the wetland hydric dynamic to different degrees. Nonetheless, the limnimetric models were calibrated for a short period, including dry years, making it necessary to extend the control period longer and validate the models under different hydroclimatic conditions. Finally, the differences between wetland functioning are explained in a conceptual hydrological model that can be useful for wetland conservation and management of related aquatic ecosystems. The understanding of the origin and fate of water in wetlands permits assessment of how future scenarios would affect hydric functioning and suggests adequate conservation measurements.
Keywords: Recursos hidráulicos - España meridional; Aguas subterráneas; Groundwater/surface–water relations; Weatlands; Southern Spain; Evaporite karst; Hydrogeological conceptual model; Evaporation; Runoff